Manajemen Strategi Peningkatan Mutu Pendidikan Di Smp Al Bayan Kota Makassar - Jumaruddin; Muhammad Ramli; Misykat Malik Ibrahim (LPPM IAIN Sorong, 2024)
The purpose of this study is to describe the strategic management approach used to improve teaching standards at Al Bayan Junior High School Makassar City. This type of research is descriptive qualitative. The data collection techniques used include notes, interviews, and observations. This research uses three activity streams for qualitative data analysis, namely data reduction, data presentation, and verification/conclusion drawing. The data triangulation technique was used in assessing the validity of the data. The findings show that: (1) Al Bayan Junior High School Makassar City conducts integrated, methodical, and comprehensive planning through the following stages in order to realize the quality of education: a) Examining the school's internal environment both material, technical, and human resources. b) Examining the geographical, social, and economic context outside the school. c) Careful observation and in-depth analysis. (2) In implementing initiatives aimed at raising educational standards, Al Irsyad leaders use the following policies: a) Continuous process improvement. b) Creating standards for school improvement and quality assurance. c) Establishing a school culture. d) Modifying the organizational structure. e) Maintaining positive interactions with customers. (3) To verify that a high-quality education program has been achieved, evaluation is also conducted in the following ways: a) by tracking all results from planning and implementing strategic management activities. b) evaluating student and individual performance. c) providing reports on how all actions were carried out; and d) making necessary corrections.